PENGARUH AKTIVITAS BELAJAR DAN KEMANDIRIAN DALAM MENGERJAKAN TUGAS TERHADAP HASIL BELAJAR SISWA EKONOMI KELAS XI DI SMA SEMEN PADANG - Arfilindo, Hagi - (Pendidikan Ekonomi, 2014)
This study aims to examine 1) the effect of learning activities on studentlearning outcomes in high school economics class XI Semen Padang, 2) Influenceof independence in doing the learning outcomes of students in high schooleconomics class XI Semen Padang, 3) The effect of learning activities andindependence in doing tasks together on learning outcomes of students in highschool economics class XI Semen Padang.When the study was conducted in May 2014. The type of research used inthis study is a descriptive study associative. The population is all students in highschool economics class XI Semen Padang many as 126 people. Samplingtechnique with Simple random sampling with a sample size of 96 people. Dataanalysis techniques of multiple linear regression analysis with SPSS version 16.0.The results showed that: 1) There is a positive and significant effect oflearning activities on student learning outcomes in high school economics classXI Semen Padang this with tcount>t table (4.955> 1.661). 2) in positive andsignificant impact of independence in doing the learning outcomes of students inhigh school economics class XI Semen Padang this is evidenced by the value oftcount>ttable (7.556> 1.661), there is a positive and significant impact jointlybetween learning activities and independence in the tasks of the learningoutcomes of students in high school economics class XI Semen Padang academicyear 2013/2014 this is evidenced by the Fcount>Ftable (135.599>3.09) and RSquare0.745.